Redescription of Leporinus jamesi (Characiformes: Anostomidae), a poorly known species of Leporinus from the lowlands of the central Amazon, Brazil - Garavello,Júlio C. (2014)
The poorly known Leporinus jamesiis redescribed. The species was originally described based on a single specimen collected in the rio Solimões at Manacapuru, in the central Amazon, Brazil. The holotype went missing before the species description was finished and published, and remained lost for more than a hundred years. Leporinus jamesi is distinguished from its congeners by having pectoral and pelvic fins dark, 42 to 45 scales on the lateral line, 16 scale series around the caudal peduncle, a body with two conspicuous dark midlateral blotches (the blotch on the caudal peduncle absent or inconspicuous), and four teeth on the premaxilla and dentary, including a bicuspid symphyseal tooth on the premaxilla. A principal component analysis on morphometric traits between combined samples of L. jamesi and L. amazonicus was performed showing significant morphometric differences between these species. In addition, inaccuracies in Borodin's descriptions of various species of the genus Leporinus are discussed.